Proanthocyanidin from Grape Seed Extracts Protects Indomethacin-Induced Small Intestinal Mucosal Injury - Dae Young Cheung; Jin Il Kim; Soo-Heon Park; Jae Kwang Kim (Gastroenterology Research and Practice)
Proanthocyanidin (grape seed proanthocyanidin extracts, GSPEs) is an antioxidant and scavenges free radicals. Excessive oxidative stress and free radical production are major components in the pathogenesis of NSAID-induced small intestinal injury. We investigated the effect of GSPEs on indomethacin-induced intestinal mucosal injury in the rat. Rats were allocated into four groups: the null control group, the indomethacin control group, the low-dose GSPEs group, and the high-dose GSPEs group. GSPEs were administered for 4 days. Then indomethacin and GSPEs were coadministered for the following 2 days by oral route. The dose of indomethacin was 200 mg/Kg. The doses of GSPEs were 100 mg/Kg for low-dose group and 300 mg/Kg for high-dose group. Luminal bleeding was solely observed in one of 5 rats from indomethacin control group. The number of ulcer count was reduced to 0.1 ± 0.3 per rat in GSPEs treated group compared to 1.4 ± 0.5 per rat in indomethacin control group. Submucosal inflammatory cell infiltration was also reduced to 50% in GSPEs treated group. The tissue level of prostaglandin E2 was not affected by GSPEs treatment. GSPEs attenuated the indomethacin-induced small intestinal injury irrespective of the tissue PGE2 depletion and glutathione consumption.